Analisis Naratif Novel Naname Yashiki No Hanzai Karya Soji Shimada - Mudiah Husnatul Aysi; Fithyani Anwar; Imelda Imelda (JURNAL ILMU BUDAYA, 2026)
This study aims to analyze the plot structure and the dynamics of conflict in Naname Yashiki no Hanzai (Pembunuhan di Rumah Miring) by Soji Shimada using Tzvetan Todorov’s narrative theory. A descriptive qualitative method with a structural literary approach is employed. The data consist of textual units representing narrative stages and conflicts, collected through close reading and note-taking techniques. The analysis applies Todorov’s five narrative stages: equilibrium, disruption, recognition of disruption, attempt to repair, and new equilibrium. The findings indicate that all five stages appear fully and coherently in the novel, with the main distinction among stages lying in the dominant type of conflict. Internal, social, and interpersonal conflicts emerge alternately in accordance with the progression of the plot. Thus, Todorov’s narrative theory is proven effective in revealing the relationship between plot structure and the development of conflict in detective fiction.